PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS PERMANAN ULAR TANGGA MUATAN IPA MATERI ALAT PERNAPASAN PADA HEWAN KELAS V SD - Rahmi Tri Handayani; Linna Afara; Anggi Citra Apriliana; Taofik (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to developt learning media based on the snakes and ladders game containing science material on respiratory organs in animals class V elementary school. This type of research is development research or R&D (Research and Development) with a research method that adapts the developmentmodel developed by ADDIE using the following five steps: Analysis, Design, Development, Implementation and Evaluation. The data collection techniques usedwere observation, interviews, and questionnaires. Based on research into the development of learning media products based on the snakes and ladders game,the results obtained from validation tests were 96% from media experts, 80% from material experts, and 87.5% from language experts. From the results of thisvalidation, the learning media based on the snakes and ladders game containing material on respiratory organs in animals meets the criteria of "good" and "verygood" so that the media is suitable to be tested on students. Based on trials with students, the results of the one to one trial were 82.66%, the small group was 90.5%, and the field test was 92.95%, from the results of the trial, the learning media based on the Snakes and Ladders game containing material on respiratory organs in animals comply the criteria of "very good".